2010
DOI: 10.1371/journal.pone.0011571
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Prosodic Speech in High Functioning Autism: A Preliminary fMRI Study

Abstract: BackgroundAutism is a neurodevelopmental disorder characterized by a specific triad of symptoms such as abnormalities in social interaction, abnormalities in communication and restricted activities and interests. While verbal autistic subjects may present a correct mastery of the formal aspects of speech, they have difficulties in prosody (music of speech), leading to communication disorders. Few behavioural studies have revealed a prosodic impairment in children with autism, and among the few fMRI studies aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 56 publications
3
42
3
Order By: Relevance
“…On the other hand, when performing semantic-pragmatic tasks, the most replicated findings include lower activation signals in the left IFG (Broca's area), prefrontal cortex, and temporo-parietal areas in brains of patients with ASD compared with controls, exhibiting functional underconnectivity and undersynchronization within these regions (Anderson et al 2010;Hesling et al 2010;Tesink et al 2009;Wang et al 2006Wang et al , 2007) (see Fig. 1, light gray bars).…”
Section: Language Processing and Communication Deficitsmentioning
confidence: 95%
“…On the other hand, when performing semantic-pragmatic tasks, the most replicated findings include lower activation signals in the left IFG (Broca's area), prefrontal cortex, and temporo-parietal areas in brains of patients with ASD compared with controls, exhibiting functional underconnectivity and undersynchronization within these regions (Anderson et al 2010;Hesling et al 2010;Tesink et al 2009;Wang et al 2006Wang et al , 2007) (see Fig. 1, light gray bars).…”
Section: Language Processing and Communication Deficitsmentioning
confidence: 95%
“…Although both ASD and neurotypical controls showed equivalent behavioral performance, the ASD group showed greater activity in the right inferior frontal gyrus, suggesting an atypical and potentially compensatory neural mechanism in individuals with ASD. A second study of pragmatic language processing found that adults with ASD showed increased activity in the left supramarignal gyrus compared with controls (Hesling et al, 2010). Several other investigations have focused on the neural correlates of prosodic cues in ASD by examining brain activity during processing of ironic vs sincere speech.…”
Section: Tom and Pragmatic Languagementioning
confidence: 99%
“…Despite similar behavioral performance between the two groups, they found increased activity of the right inferior frontal gyrus (rIFG) in the ASD group (as compared to neurotypical controls), suggesting a compensatory mechanism for making inferences based on prosodic cues. Another recent study investigating the neural correlates of prosodic speech comprehension (Hesling et al, 2010) found a greater reliance on the left supramarginal gyrus when processing prosodic information in individuals with ASD relative to controls.…”
mentioning
confidence: 99%